2020
DOI: 10.3390/s20133734
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Full-Duplex V2V-VLC in Rectilinear and Curved Roadway Scenarios

Abstract: We study here the vehicle-to-vehicle (V2V) visible light communication (VLC) between two cars moving along different roadway scenarios: (i) a multiple-lane rectilinear roadway and (ii) a multiple-lane curvilinear roadway. Special emphasis was given to the implementation of full-duplex (FD) cooperative communication protocols to avoid communication disruption in the absence of a line-of-sight (LOS) channel. Importantly, we found that the cooperative FD V2V-VLC is promising for avoiding communication dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…Another very important aspect that results from the experimental tests is related to the fact that the VLC technology is able to provide V2V connectivity, even in vehicle misalignment conditions. Although the issues related to the effect of vehicle misalignment on V2V VLC performances have been theoretically analyzed in other works [ 49 , 50 , 57 , 58 ], this is the first work that provides a consistent experimental evaluation of such a scenario, while providing a step by step comparison with the case when the vehicles are aligned. The authors of [ 44 ] provide a highly valuable experimental demonstration of a V2V VLC link in mobile conditions, and identify the distance and the incidence angle as the two main problems affecting the performances of such connections.…”
Section: Discussion On the Results Contributions Of This Work And Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Another very important aspect that results from the experimental tests is related to the fact that the VLC technology is able to provide V2V connectivity, even in vehicle misalignment conditions. Although the issues related to the effect of vehicle misalignment on V2V VLC performances have been theoretically analyzed in other works [ 49 , 50 , 57 , 58 ], this is the first work that provides a consistent experimental evaluation of such a scenario, while providing a step by step comparison with the case when the vehicles are aligned. The authors of [ 44 ] provide a highly valuable experimental demonstration of a V2V VLC link in mobile conditions, and identify the distance and the incidence angle as the two main problems affecting the performances of such connections.…”
Section: Discussion On the Results Contributions Of This Work And Perspectivesmentioning
confidence: 99%
“…The efficacy of this method has been intensively investigated in indoor VLC applications [ 18 , 19 ]. This solution has also been found to be suitable in inter-vehicle applications and the results showed that the connectivity on curved roads can be improved with the help of a relay vehicle [ 58 ]. Experimental demonstrations of the usage of relay-assisted VLC in vehicular applications are available in [ 68 , 69 ].…”
Section: Discussion On the Results Contributions Of This Work And Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…For indoor applications, there exists a wide variety of applications, such as extending the capacity and complementing the radio frequency (RF) systems [ 5 ], positioning and resource monitoring [ 6 , 7 ], intruder detection [ 8 ] or providing coverage where RF transmission is not allowed [ 9 ], among others. Outdoor VLC applications comprise vehicle-to-vehicle communications [ 10 , 11 , 12 ] or some trials and analysis for long distance transmission [ 13 , 14 , 15 ]. In this context, VLC have been standardized as 802.15.7 [ 16 ], and considering their integration in the IP network, usually referred to as light fidelity (LiFi), under the standard 802.11 bb [ 17 ].…”
Section: Introductionmentioning
confidence: 99%